Palladium‐Catalyzed Construction of Phthalides Bearing Two Adjacent Stereocenters through Retro‐oxa‐Michael Addition - Liu, Li‐Xia; Niu, Tong; Bai, Yu‐Qing; Zhou, Yong‐Gui (Chinese journal of chemistry, 2024)
Comprehensive Summary Optically active phthalides are prevalent in many natural and bioactive products. Herein, a novel dynamic kinetic resolution of isobenzofuranone derivatives through palladium‐catalyzed asymmetric allylic alkylation has been developed to synthesize phthalide derivatives bearing vicinal quaternary and tertiary stereocenters with high yields, showing excellent chemo‐, enantio‐ and diastereoselectivity. Furthermore, gram‐scale experiment underwent smoothly and the transformation of product could build a bridged bicyclic skeleton. A novel dynamic kinetic resolution of isobenzofuranone derivatives through palladium‐catalyzed asymmetric allylic alkylation has been developed to synthesize phthalide derivatives bearing vicinal quaternary and tertiary stereocenters with high yields, showing excellent chemo‐, enantio‐ and diastereoselectivity.